Synthetic transmembrane DNA receptors enable engineered sensing and actuation - Ze-Rui Zhou; Man-Sha Wu; Zhenglin Yang; Yuting Wu; Weijie Guo; Da-Wei Li; Ruo-Can Qian; Yi Lu (Nature Communications)
Abstract In living organisms, cells synergistically couple cascade reaction pathways to achieve inter- and intracellular signal transduction by transmembrane protein receptors. The construction and assembly of synthetic receptor analogs that can mimic such biological processes is a central goal of synthetic biochemistry and bionanotechnology to endow receptors with user-defined signal transduction effects. However, designing artificial transmembrane receptors with the desired input, output, and performance parameters are challenging. Here we show that the dimerization of synthetic transmembrane DNA receptors executes a systematically engineered sensing and actuation cascade in response to external molecular signals. The synthetic DNA receptors are composed of three parts, including an extracellular signal reception part, a lipophilic transmembrane anchoring part, and an intracellular signal output part. Upon the input of external signals, the DNA receptors can form dimers on the cell surface triggered by configuration changes, leading to a series of downstream cascade events including communication between donor and recipient cells, gene transcription regulation, protein level control, and cell apoptosis. We believe this work establishes a flexible cell surface engineering strategy that is broadly applicable to implement sophisticated biological functions.